Factors Affecting Medical Adherence in Patients with Coronary Heart Disease - Gina Nurdina; Tita Daulati; Herdiman Herdiman (STIKep PPNI Jawa Barat, 2023)
Aims: The problems with Coronary Heart Disease (CHD) is non-adherence to taking medication which results in further complications. Only 80% of patients with chronic diseases living in developed countries follow treatment recommendations in taking medication. The factors that influence the previous research are knowledge, attitudes, and family support. However, in this study, there were different factors examined, namely age, gender, last education level, length of illness, and self-efficacy. Objective: This study aimed to determine the factors that influence medication adherence in patients with coronary heart disease (CHD). Method: this type of research is quantitative with a cross-sectional study approach. The population in this study were all patients with coronary heart disease who came for routine checkups at the Cardiac Polyclinic of RSAU Dr. M. Salamun Bandung with a sample of 67 people, with a convenience sampling technique. Data collection techniques used the Demographic Characteristics questionnaire, MMAS-8, PSS-Fa, and CSE. Results: In this study, there were significant results between age (0.000), suffering from an illness (0.004), self-efficacy (0.001), and family support (0.029) with medication adherence in patients with coronary heart disease. Conclusion: It can be concluded that the factors that have the most influence are the burden of suffering from the disease and those that do not affect adherence to taking medication in CHD patients, namely gender, and the last level of education.